![\large\underline{\sf{Solution-}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/auxvkffb37ppkivojcb9qg05yjvnvge1dw.png)
Consider LHS
![\rm :\longmapsto\: \sqrt{(secx + 1)/(secx - 1) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/onog0rdxrs551gnlru6dnfcvx6shpwatp4.png)
can be rewritten as
![\rm \: = \: \sqrt{((1)/(cosx) + 1 )/((1)/(cosx) - 1) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/ctduvdan5yvp1k2zenabidd4pyeru2zj0c.png)
![\rm \: = \: \sqrt{((1 + cosx)/(cosx))/((1 - cosx)/(cosx)) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/ai35f665td3zp19gnlbro7wyj6o60vqyzy.png)
![\rm \: = \: \sqrt{(1 + cosx)/(1 - cosx) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/oigas4247q4sysobyeh5tw3d9tximaukwg.png)
On rationalizing the numerator, we get
![\rm \: = \: \sqrt{(1 + cosx)/(1 - cosx) * (1 - cosx)/(1 - cosx) }](https://img.qammunity.org/2022/formulas/mathematics/high-school/wzrqtcfu8sijqszaonxk1htx3ccyr54hi0.png)
![\rm \: = \: \sqrt{\frac{1 - {cos}^(2) x}{ {(1 - cosx)}^(2) } }](https://img.qammunity.org/2022/formulas/mathematics/high-school/ta0cshqvcjqo83bgu87dkgiuyg2j3v75vg.png)
We know,
![\red{\rm :\longmapsto\:\boxed{\tt{ {sin}^(2)x + {cos}^(2)x = 1}}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/i33y5ijfwru1oc6egnfjsw27g5ve1is8o0.png)
So, using this, we get
![\rm \: = \: \frac{ \sqrt{ {sin}^(2) x} }{1 - cosx}](https://img.qammunity.org/2022/formulas/mathematics/high-school/tpgnqt19d303l5no6e31sd9czmejm1rglc.png)
![\rm \: = \: ( sinx )/(1 - cosx)](https://img.qammunity.org/2022/formulas/mathematics/high-school/kr56afnqpezqimdib6y83z6mt7goqwkk1t.png)
![\rm \: = \: (1)/( \: \: \: \: (1 - cosx)/(sinx) \: \: \: \: )](https://img.qammunity.org/2022/formulas/mathematics/high-school/jsd2uay772qejd5svq44e73jffjnuaycbz.png)
![\rm \: = \: (1)/( \: \: \: \: (1)/(sinx) - (cosx)/(sinx) \: \: \: \: )](https://img.qammunity.org/2022/formulas/mathematics/high-school/d1fj36671nvpuyfxvz8q1ntv3jehcbgvuh.png)
![\rm \: = \: (1)/( \: \: \: \: cosecx - cotx \: \: \: \: )](https://img.qammunity.org/2022/formulas/mathematics/high-school/9yb9xpwuhbh67jg89cunxz66yauaghtxgo.png)
Hence, Proved
![\rm \implies\:\: \boxed{\tt{ \sqrt{(secx + 1)/(secx - 1) } = (1)/(cosecx - cotx)}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/88mj17a8tg5dclmnxl66lr52rbfpr4ighy.png)
▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬
MORE TO KNOW
Additional Information:-
Relationship between sides and T ratios
sin θ = Opposite Side/Hypotenuse
cos θ = Adjacent Side/Hypotenuse
tan θ = Opposite Side/Adjacent Side
sec θ = Hypotenuse/Adjacent Side
cosec θ = Hypotenuse/Opposite Side
cot θ = Adjacent Side/Opposite Side
Reciprocal Identities
cosec θ = 1/sin θ
sec θ = 1/cos θ
cot θ = 1/tan θ
sin θ = 1/cosec θ
cos θ = 1/sec θ
tan θ = 1/cot θ
Co-function Identities
sin (90°−x) = cos x
cos (90°−x) = sin x
tan (90°−x) = cot x
cot (90°−x) = tan x
sec (90°−x) = cosec x
cosec (90°−x) = sec x
Fundamental Trigonometric Identities
sin²θ + cos²θ = 1
sec²θ - tan²θ = 1
cosec²θ - cot²θ = 1